A Numerical Study of Sheet Flow Under Monochromatic Nonbreaking Waves Using a Free Surface Resolving Eulerian Two‐Phase Flow Model. Issue 7 (5th July 2018) - Kim, Yeulwoo; Cheng, Zhen; Hsu, Tian‐Jian; Chauchat, Julien
Abstract: We present a new methodology that is able to concurrently resolve free surface wavefield, bottom boundary layer, and sediment transport processes throughout the entire water column. The new model, called SedWaveFoam, is developed by integrating an Eulerian two‐phase model for sediment transport, SedFoam, and a surface wave solver, InterFoam/waves2Foam, in the OpenFOAM framework. SedWaveFoam is validated with a large wave flume data for sheet flow driven by monochromatic nonbreaking waves. To isolate the effect of free surface, SedWaveFoam results are contrasted with one‐dimensional‐vertical SedFoam results, where the latter represents the oscillating water tunnel condition. Results demonstrate that wave‐averaged total sediment fluxes in both models are onshore‐directed; however, this onshore transport is significantly enhanced under surface waves. Onshore‐directed near‐bed sediment flux is driven by a small mean current mainly associated with velocity skewness. More importantly, progressive wave streaming drives onshore transport mostly in suspended load region due to an intrawave sediment flux. Further analysis suggests that the enhanced onshore transport in suspended load is due to a "wave‐stirring" mechanism, which signifies a nonlinear interaction between waves, streaming currents, and sediment suspension. We present some preliminary efforts to parameterize the wave‐stirring mechanism in intrawave sediment transport formulations. Key Points: A new modeling methodology to resolve free surface waves and sediment transport with an Eulerian two‐phase flow approach is presented The effects of progressive wave streaming on bottom boundary layer and sediment transport are isolated by model experiments Enhanced onshore sediment transport under surface waves associated with progressive wave streaming is due to a wave‐stirring mechanism